2004
DOI: 10.1002/mrm.20268
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of T using a multislice spin‐lock pulse sequence

Abstract: A multislice spin-lock (MS-SL) pulse sequence is implemented on a clinical scanner to acquire multiple images with spin-lockgenerated contrast of the knee joints of six healthy human subjects. The MS-SL sequence produces images with T 1 contrast with an additional factor of intrinsic T 2 weighting, which hinders direct measurement of T 1 . A method is presented to compensate the MS-SL-generated data with regard to T 2 in an effort to accurately calculate multislice T 1 maps in a feasible experimental time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…For example, at 4.7 T glycerol formal's protons have a frequency difference ∆ν ≈ 16 Hz; hence ν opt n ≈ 80 Hz is sufficient to achieve significant singlet-state lifetime enhancement. For common biomolecules such as citric acid and aspartic acid, ν opt n < 100 Hz at 1.5 T, which is well within the spin-locking regime commonly used in clinical MRI [27,28]. The spin-locking times and strengths used in [27,28] imply that a 60 Hz spin-lock could be safely applied for 3.5 s, and a 20 Hz spin-lock for 30 s. These timescales are of the same order as the singlet lifetimes we measured for typical small molecules, and thus should be sufficient to conduct a variety of in vivo measurements using singlets.…”
Section: Discussionmentioning
confidence: 83%
“…For example, at 4.7 T glycerol formal's protons have a frequency difference ∆ν ≈ 16 Hz; hence ν opt n ≈ 80 Hz is sufficient to achieve significant singlet-state lifetime enhancement. For common biomolecules such as citric acid and aspartic acid, ν opt n < 100 Hz at 1.5 T, which is well within the spin-locking regime commonly used in clinical MRI [27,28]. The spin-locking times and strengths used in [27,28] imply that a 60 Hz spin-lock could be safely applied for 3.5 s, and a 20 Hz spin-lock for 30 s. These timescales are of the same order as the singlet lifetimes we measured for typical small molecules, and thus should be sufficient to conduct a variety of in vivo measurements using singlets.…”
Section: Discussionmentioning
confidence: 83%
“…Several preliminary studies have demonstrated this feasibility of in vivo T1r-weighted imaging of articular cartilage [28][29][30] and the spine 13,14 . This study was also limited to twodimensional magnetic resonance scans acquired at the midsagittal section of the disc, with which it would be difficult to register locations across sequential imaging sessions in an in vivo longitudinal study.…”
Section: Discussionmentioning
confidence: 96%
“…Small variations in T 1r dispersion profiles were observed in spectroscopic studies of cartilage specimens (229). However, except for a constant shift, there were no significant changes observed in the T 1r dispersion curve with varying levels of GAG depletion by trypsin (25).…”
Section: T 1r Dispersion In Cartilagementioning
confidence: 88%
“…In one of the spectroscopic studies of T 1r dispersion in bovine cartilage, it was suggested that the exchange between protons on -OH and -NH of GAG with bulk water may be the dominant source for the low frequency (0-1.5 kHz) T 1r dispersion in cartilage (229). Low-frequency dispersion changes are correlated with loss of PG from the ECM of cartilage.…”
Section: T 1r Dispersion In Cartilagementioning
confidence: 99%